Defending the witness - Stover, Sharee (Love inspired suspense., 2023)
"After witnessing a murder at the hands of a notorious gang leader, Ayla DuPree is a marked woman sent straight to witness protection. But when her handler is killed and her safety compromised, she has no choice but to run forcing US Marshal Chance Tavalla and his K-9 to chase her. Can Chance keep Ayla alive long enough to find safety and justice?"--Page 4 of cover.